Seismic-Wave Scattering, Imaging, and Inversion (Communications in Computational Physics, 2020)
Ru-Shan Wu has made seminal contributions in many research areas ingeophysics, such as seismic-wave propagation, scattering, imaging, and inversion.We highlight some of his research in holography imaging, diffraction tomography,seismic-wave scattering and its applications to studying Earth's heterogeneity, one-way wave propagation and one-return wave modeling, beamlet and dreamlet applications, strong non-linear full-waveform inversion, and direct envelop inversion.